Pengaruh Pendidikan dan Pelatihan Terhadap Kinerja Pegawai di PUSKESMAS Besuk Kecamatan Besuk Kabupaten Probolinggo - Junaidi -; Herlin Herawati; Syamsul Hidayatullah (Ecobuss, 2016)
This research was conducted at Puskesmas Besuk with the aim to know the effect simultaneously and partially between education and training on performance of health officer of Puskesmas Besuk Probolinggo regency, and to know which variables have dominant effect. Independent variables in the form of education and training, and the dependent variable is the performance of employees. The sample used is 32 people, and the method of data analysis using quantitative analysis method by using statistical formula in the form of multiple regression analysis, multiple correlation, coefficient of determination and hypothesis testing. The results showed that education and training have an effect on the employee performance shown by the result of multiple regression analysis Y = 4,329 + 0,516 X1 + 0,294 X2. From the results of hypothesis testing "There is a significant influence simultaneously between education and training on the performance of employees of Puskesmas Besuk Probolinggo regency". From the results of partial hypothesis testing (individual) "There is a partial significant influence between education and training on the performance of Puskesmas employees". From the result of multiple regression analysis, it is known that regression coefficient b1 (0,516) is bigger than regression coefficient b2 (0,294), so it proved that "Educational variable that has dominant influence to performance of health officer of Puskesmas Besuk Probolinggo regency". Keyword : education, training, performance.